2011
DOI: 10.1186/1471-2458-11-619
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and self-rated health: a cross-sectional study of 3,601 citizens of Athens, Greece

Abstract: BackgroundSelf-rated health (SRH) is a popular health measure determined by multiple factors. International literature is increasingly focusing on health-related behaviors such as smoking, dietary habits, physical activity, even religiosity. However, population-based studies taking into account multiple putative determinants of SRH in Greece are scarce. The aim of this study was to clarify possible determinants of SRH with an emphasis on the relationship between SRH and lifestyle variables in a large sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
38
5
7

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 40 publications
10
38
5
7
Order By: Relevance
“…Sleep quality, although differently assessed in various studies, seems to have an important relationship with feeling of fresh and attentive. These results are in agreement with previous studies [18][19][20] . BMI is another important indicator of health status.…”
Section: Discussionsupporting
confidence: 94%
“…Sleep quality, although differently assessed in various studies, seems to have an important relationship with feeling of fresh and attentive. These results are in agreement with previous studies [18][19][20] . BMI is another important indicator of health status.…”
Section: Discussionsupporting
confidence: 94%
“…In general, the result of this study is consistent with previous findings that quality of sleep positively affects health (e.g., Darviri et al, 2011;Hale et al, 2013). Numerous studies also provide evidence that vigorous physical activity is related to fewer negative psychological symptoms and to increased mental health (e.g., Buman et al, 2010;Harvey et al, 2010).…”
Section: Discussionsupporting
confidence: 83%
“…Along with the benefits of involvement in physical activity, researchers have considered the quality of sleep, diet, and tobacco use in relation to health (e.g., Darviri et al, 2011;Reid et al, 2006;Sodergren et al, 2012). These authors concluded that the quality of sleep, diet and non-smoking positively and closely associate with health.…”
Section: Introductionmentioning
confidence: 99%
“…Os resultados também demonstraram que a inatividade física foi estatisticamente associada à pior autoavaliação de saúde. Tais resultados são condizentes com dados da literatura 22,23 reforçam as evidências de que os indivíduos que mantêm um estilo de vida mais saudável tendem a autoavaliar melhor seu estado de saúde quando comparados com aqueles que não o fazem 31 . Apesar disso, essa investigação não encontrou significância estatística entre o tabagismo ou o consumo de álcool e a pior autoavaliação de saúde.…”
Section: Resultsunclassified